Animation Media on Human Digestive System Material for Fifth-Grade Elementary School Students - Juniarti, Ni Nyoman Esti; Bayu, Gede Wira; Sudatha, I Gde Wawan (International Journal of Elementary Education, 2021)
The lack of understanding of the learning material has an impact on the results of student learning. Teachers only depend on a single source, textbooks, so it is pretty tricky for students to learn abstract material. In addition, teachers in teaching and learning activities only use conventional methods to focus on the teacher, not the students. This study aims to develop animated video learning media on the human digestive system material for fifth-grade elementary school. Media development in research uses the ADDIE model, which includes the Analyze, Design, Development, Implementation, and Evaluation stages. The data collection method in this study used a questionnaire method and a rating scale instrument—the data analysis technique used qualitative descriptive statistical data analysis and quantitative descriptive statistics. The study result showed the calculation result of the average validity test score; the result is that the percentage obtained in terms of the material as a whole is 95.71%. The percentage of learning material experts is 90-100 with outstanding qualifications and does not need to be revised. Calculating the percentage of the validity test in terms of the overall design is 94.61%. The percentage of learning design experts is 90-100 with outstanding qualifications and does not need to be revised. From the average score in terms of media experts, it was stated that the learning media had outstanding qualifications with 92.93%. Meanwhile, from the practitioner test, it was stated that the learning media had outstanding qualifications with an overall percentage of 100%. So, animated video learning media is feasible to use in learning. This research implies that animated video media can help students in the learning process.